Marian Apparitions and Devotions: the formation of a visionary culture in Portugal and its uses in the Catholic Restoration project (1917-1950) (Tempo e Argumento, 2022)
The narratives about the Marian apparitions marked part of the projects of the members of the Catholic Church in the first half of the 20th century.  From the formation of a visionary culture, the events in Portugal were used to react to secularism and anticlericalism instituted after the implementation of the Republic.  In this sense, through the Cultural History of Religions' approach, we analyze how Marian events were important for the transnational projects of ecclesiastics and intellectuals between 1917 and 1950. In order to do this analysis, we used press materials, religious documents, and characters' memories, with the goal of understanding the narratives surrounding religious events.  Furthermore, we consider that part of the ecclesiastical hierarchy collaborated with the formation of a visionary network, with projects in different territorial spaces, fundamental for the reaffirmation of religious ideas in the established time frame.Keywords: Marian Apparitions; Transnational Histories; 20th century.